Dollar Safety and the Global Financial Cycle - Jiang, Zhengyang; Krishnamurthy, Arvind; Lustig, Hanno (Review of Economic Studies, 2024)
Abstract We develop a model of the global financial cycle with one key ingredient: the international demand for safe dollar assets. The model matches patterns of dollar borrowing and currency mismatch, the U.S. external balance sheet, exorbitant privilege, spillovers of the U.S. monetary policy to the rest of the world, and the dollar as a global risk factor. In doing so, we lay out a novel transmission mechanism through which the U.S. monetary policy affects the currency market and the global economy. The global financial cycle is a dollar cycle.